Chondroid Tumors as Incidental Findings and Differential Diagnosis between Enchondromas and Low-grade Chondrosarcomas - Afonso, P Diana; Isaac, Amanda; Villagrán, José Martel (Seminars in musculoskeletal radiology, 2019)
Chondroid tumors are a heterogeneous group of neoplasms that all share the production of chondroid matrix. This ranges from a fetal type to mature hyaline cartilage and mirrors its imaging characteristics.The benign chondroid tumors represent some of the most encountered incidental bone lesions, with osteochondroma the most frequent benign bone tumor. Enchondroma is mostly asymptomatic, and yet it is probably the second most common primary bone tumor. Similarly, its malignant counterpart, chondrosarcoma, is the second most common malignant primary bone tumor.The 2013 World Health Organization (WHO) updated this group of tumors, and grade 1 chondrosarcoma was renamed "atypical cartilage tumor" and classified as an intermediate type of tumor, not a malignancy, which better describes its clinical behavior.In this article we summarize changes made in the updated 2013 WHO classification and highlight the diagnostic features differentiating an enchondroma from a low-grade chondrosarcoma. We also describe practical imaging aspects of the remaining chondroid tumors.